Rak mod - znanje in stališča mladih moških - Lokar, Katarina (Obzornik zdravstvene nege, 2001)
The article presents the results of the research about knowledge and attitudesof young men about testicular cancer. In the introduction, problems concerning testicular cancer are described. Primary goals of this research areto find out how much young men know about testicular cancer, what are theirattitudes toward testicular cancer, to what extend do they know and perform testicular self-examination and how much are they motivated to increase the knowledge about this subject. In the research participated 42 young men. Research data were collected with questionnaires and were analized with descriptive statistical method. Results of the research showed insuficient knowledge of participants about testicular cancer, one half of participants had positive attitudes about testicular cancer issues and one third of them neutral attitudes, two thirds of participants had already heard about testicular self-examination and one third of them had performed it. Mostof participants were also very motivated for extending the knowledge abouttesticular cancer and about testicular self-examination.
Keywords: Health education; man; moški; rak (medicina); Self-examination; Testicular neoplasms; zdravstvena vzgoja